RANCANG BANGUN PENGUAT SEBAGAI ANTARMUKA STETOSKOP DENGAN KOMPUTER PRIBADI - Yudianingsih, Yudianingsih (Universitas Respati Yogyakarta, 2012)
This research is purposed to get a stetoscope amplifier circuit which used to CPU interface. Stetoscope is used to early diagnostic aspecially for breathing disorder and heart sound disorder. This research is resulting an amplifier with 1kHz cut-off frequency, 120 dB/decade slope, maximum gain 8800 times, and 1Vpp output voltage. It is used 9 V power supply.The frequency response of sensor is between 20 Hz to 4kHz. It could to recording heart sound signal with CPU, with connecting the amplifier to audio-input in CPU. Then the recorded data could be analized with any algorithm. Keyword: Stetoscope, Amplifier, Gain, Frequency response.